1985
DOI: 10.1002/pros.2990060411
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of prostatic cancer by matched‐pair analysis

Abstract: In 1976, we designed an original questionnaire, consisting of 111 questions, directed at the epidemiology of prostatic disease. A case-control study by matched-pair analysis was conducted on 100 controls matched for age within 1 year and for residence in the same prefecture. Patients with prostatic cancer were distinguished from the general population of men by the following characteristics: 1) belonging to middle or lower socioeconomical class, 2) marriage at a young age and a long married life, 3) precocity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(22 citation statements)
references
References 26 publications
1
20
1
Order By: Relevance
“…These findings appear difficult to reconcile with the observation that prostate cancer risk is low in populations that consume large amounts of EPA-and DHA-containing fish and seafood (64,66,123), and with a case-control study performed in England, which also demonstrated a protective effect of high fish consumption (124). However, more recently a casecontrol study from North Carolina found that the levels of LA, but not a-linolenic acid, in erythrocyte membranes and adipose tissues were associated with an increased risk of prostate cancer; only the highest level of EPA was related to a decreased risk (125).…”
Section: Dietary Fat and Fatty Acids In Prostate Cancercontrasting
confidence: 45%
“…These findings appear difficult to reconcile with the observation that prostate cancer risk is low in populations that consume large amounts of EPA-and DHA-containing fish and seafood (64,66,123), and with a case-control study performed in England, which also demonstrated a protective effect of high fish consumption (124). However, more recently a casecontrol study from North Carolina found that the levels of LA, but not a-linolenic acid, in erythrocyte membranes and adipose tissues were associated with an increased risk of prostate cancer; only the highest level of EPA was related to a decreased risk (125).…”
Section: Dietary Fat and Fatty Acids In Prostate Cancercontrasting
confidence: 45%
“…Not surprisingly, therefore, results from studies of recalled timing of puberty and PCa have tended to be mixed and generally inconclusive. 11, 12, 19, 82, 83, 85, 92, 106110 Although future research into this biologically plausible hypothesis is certainly warranted, better methods for ascertaining age at onset of puberty in men are needed. It should also be recognized that, as for early-adulthood BMI, the value of further study is limited to insight into the timing and mechanisms of PCa development and possible chemoprevention strategies.…”
Section: Summary Of Early-life Epidemiological Studiesmentioning
confidence: 99%
“…83, 94, 106, 125 These include studies of rheumatic fever, tonsillectomy, appendectomy, measles, mumps, and other several other infections. Although findings for most of these infections and procedures were null, positive associations were observed for rheumatic fever 106, 125 and tonsillectomy, 125 both of which are, interestingly, related to Streptococcus pyogenes . Rheumatic fever is a now rare complication of S. pyogenes infection and tonsillectomy is performed frequently for S. pyogenes tonsillitis.…”
Section: Sexual Activity and Infectionsmentioning
confidence: 99%
“…Most [28,31,, but not all [16,32] studies of diabetes and prostate cancer that were conducted before the use of PSA screening [28,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] or studies that were carried out in countries without universal PSA screening [16,31,32,[65][66][67][68][69][70] found no association between diabetes and prostate cancer. In contrast, investigations that were conducted after the use of PSA screening fairly consistently reported an inverse association between diabetes and prostate cancer [25-27, 29, 71-74].…”
Section: Discussionmentioning
confidence: 99%